Absence of chronic hepatitis E in a German cohort of common variable immunodeficiency patients - Sven Pischke; Ruediger Horn-Wichmann; Diana Ernst; Bjoern Georg Meyer; Regina Raupach; Gerrit Ahrenstorf; Reinhold Ernst Schmidt; Michael Peter Manns; Torsten Witte; Heiner Wedemeyer (MDPI AG, 2012)
Cases of chronic or prolonged hepatitis E virus (HEV) infections have been described in solid organ transplant recipients, HIV infected patients and in patients with malignancies or idiopathic CD4+ T lymphopenia. It is unknown if HEV infection also takes chronic courses in patients with common variable immunodeficiency (CVID). We studied a cohort of 73 CVID patients recruited in a low endemic Central European country. None of the subjects tested positive for HEV RNA or anti-HEV IgG. Immunoglobulin transfusions (n=10) tested negative for HEV RNA but all were anti-HEV positive. To verify that such pooled blood products contain anti-HEV protective antibodies we measured the anti-HEV IgG optical density (OD) values in patients before and after transfusion. Anti-HEV OD values increased after infusion but did not reach the cut-off considered as positive. Thus, chronic HEV infections seem to be rare events in CVID patients in Germany. Commercially available immuno globulin infusions contain anti HEV antibodies and may contribute to protection from HEV infection